The Zimbabwe wildlife industry: a brief overview - La Grange, N. J., author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
1. History - Brief overview of the origins of the wildlife industry in Zimbabwe, including Operation Noah, and the formation of the Parks and Wildlife Department. 2. Introduction of the 1975 Parks and Wildlife Act - what this meant for the industry and what the consequences of this decision were. 3. CAMPFIRE - The Act was amended to include communal areas and the people living in those areas, which allowed the birth of CAMPFIRE. 4. Growth of the Industry – private landowners invested heavily in wildlife, hunting and tourism boomed, Zimbabwe became an example of what could be done. 5. Role of the Veterinary Department -regulating movements of certain animals became necessary; policies were established to protect EU beef exports. Formation of Wildlife Unit. 6. Changing policies - the effects of the land redistribution drive. Formation of new policies, and the subsequent changing face of the industry. 7. Current Role Players - the various groups involved, the motivation out of passion for wildlife. Zimbabwe Wildlife Association. 8. Conservancies - highlighting the success of large areas designated for wildlife use, the challenges and opportunities. 9. Cecil! The aftermath, consequences, and the power of social media. 10. Ethics and transparency - with the spotlight now on us, we need to be careful. 11. Looking forward - what lies ahead will be determined by the attitudes and determination of those involved. Zimbabwe relies heavily on the tourism and hunting industry, and so we need to find ways of supporting the wildlife industry through unity and a common goal. Zimbabwe - once a proud leader in the wildlife industry - has lost its place on the pedestal of world conservation. However all is not lost. Through the passion and determination of its people, Zimbabwe is trying to reclaim its rightful place again. As humans and wildlife struggle for existence at the coal face, the things that are beneficial, and those that are detrimental, become apparent. The lessons learnt will help carry the industry forward, and others will be able to draw on our experiences.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.